AdoMet triggers apoptosis in head and neck squamous cancer by inducing ER stress and potentiates cell sensitivity to cisplatin. Issue 8 (21st December 2018) - Mosca, Laura; Pagano, Martina; Ilisso, Concetta Paola; Cave, Donatella Delle; Desiderio, Vincenzo; Mele, Luigi; Caraglia, Michele; Cacciapuoti, Giovanna; Porcelli, Marina
Abstract: S‐Adenosyl‐l ‐methionine (AdoMet) is a naturally and widely occurring sulfonium compound that plays a primary role in cell metabolism and acts as the principal methyl donor in many methylation reactions. AdoMet also exhibits antiproliferative and proapoptotic activities in different cancer cells. However, the molecular mechanisms underlying the effects exerted by AdoMet have only been partially studied. In the current study, we evaluated the antiproliferative effect of AdoMet on Cal‐33 oral and JHU‐SCC‐011 laryngeal squamous cancer cells to define the underlying mechanisms. We demonstrated that AdoMet induced apoptosis in Cal‐33 and JHU‐SCC‐011 cells, involving a caspase‐dependent mechanism paralleled by an increased Bax/Bcl‐2 ratio. Moreover, we showed, for the first time, that AdoMet induced ER‐stress in Cal‐33 cells and activated the unfolded protein response, which can be responsible for apoptosis induction through the activation of CHOP and JNK. In addition, AdoMet‐induced ER‐stress was followed by autophagy with a consistent increase in the levels of the autophagic marker LC3B‐II, which was indeed potentiated by the autophago‐lysosome inhibitor chloroquine. As both escape from apoptosis and decreased activation of JNK are mechanisms of resistance to cisplatin (cDPP), an agent usually used in cancer therapy, we have evaluated the effects of AdoMet in combination with cDPP on Cal‐33 cells. Our data showed that the combined treatment resulted in a strong synergism in inhibiting cell proliferation and in enhancing apoptosis via intrinsic mechanism. These results demonstrate that AdoMet has ER‐stress‐mediated antiproliferative activity and synergizes with cDDP on cell growth inhibition, thus providing the basis for its use in new anticancer strategies. Abstract : AdoMet induced apoptosis and ER stress involving a caspase‐dependent mechanism paralleled by an increased Bax/Bcl‐2 ratio and activation of CHOP and JNK in oral cancer cells. AdoMet‐induced ER stress was followed by autophagy with a consistent increase in the levels of the autophagic marker LC3B‐II, which was indeed potentiated by the autophago‐lysosome inhibitor chloroquine. The combined treatment between AdoMet and cisplatin resulted in a strong synergism in inhibiting cell proliferation and in enhancing apoptosis via intrinsic mechanism.